Studi Deskriptif Kepercayaan Diri Mahasiswa Psikologi Universitas Negeri Padang - Putri, Sylvia Ananda; Yusra, Zulmi (Indo-MathEdu Intellectuals Journal, 2025)
The problem found that the lack of self-confidence among students is caused by several problems, one of which is academic pressure. On average, students say that the lack of self-confidence arises when they have to speak in public. This study aims to describe the self-confidence of psychology students in general. This study uses a descriptive quantitative method. The scale used according to Lauster modified by Nurhuda (2019) is belief in one's own abilities, optimistic, objective, responsible, rational and realistic. The population of this study were students of the psychology department, the sampling technique used stratified proportional random sampling, so that the sample in this study amounted to 104 people. The data was analyzed using the one sample t-test analysis technique. The research results show that students have a medium level of self-confidence with a percentage of 90%.